A facile strategy to achieve fully bio-based epoxy thermosets from eugenol. Issue 16 (29th July 2019) - Chen, Chien-Han; Tung, Shih-Huang; Jeng, Ru-Jong; Abu-Omar, Mahdi M.; Lin, Ching-Hsuan
Abstract : Fully bio-based epoxy thermosets can be achieved by the reaction of active esters and epoxide in eugenol-derived epoxy compounds. Abstract : To achieve sustainability, many kinds of bio-based epoxy resins have been developed. However, to the best of our knowledge, a 100% bio-based epoxy thermoset has rarely been reported since it needs both the epoxy resin and curing agent to be bio-based. This work provides a facile strategy to achieve epoxy thermosets with 100% bio-based content. The strategy includes the preparation of four bio-based epoxy resins1–4 and their thermosets through the self-curing reaction of1–4 . The epoxy compounds1–4 were prepared from the esterification of eugenol with succinyl, adipoyl, suberoyl, and 2, 5-furan chloride, respectively, followed by the oxidation of the allylic bond. Through NMR, DSC, and FTIR analyses, we confirm that the self-curing reaction of1–4 occurred through a 4-dimethylpyridine (DMAP)-catalyzed reaction of active esters and epoxides. This work successfully provides a facile strategy to achieve fully bio-based epoxy thermosets.